IMPLEMENTASI STRATEGI HUMAS DPRD SURAKARTA DALAM MEDIA SOSIAL INSTAGRAM - Oktaviastuti, Tassya Pratiwi; Wisudawanto, Rahmat; Ningsih Rahayu Putri, Sofia (JURNAL KOMUNITAS, 2024)
The Surakarta DPRD (parliament) Public Relations utilizes Instagram social media to implement public relations strategies in building public opinion. The use of Instagram social media by the Surakarta DPRD public relations in publishing activities is less able to implement a public relations strategy. It can be seen from un up to date Instagram uploads of the Surakarta DPRD of their activities to build public opinion. The research aims to explain the implementation of the Surakarta City DPRD's public relations strategy on Instagram social media. This study used an analysis of public relations strategy theory from Cutlip, Center, and Broom (Ruslan, 2006: 351), which consists of four stages, namely, fact finding, planning, communication, taking action, and evaluation. This research was a descriptive qualitative research with primary data sources in the form of uploads on the Instagram account @dprd.kota.surakarta and secondary data in the form of informants selected based on a purposive sampling technique.This study used three methods of data collection techniques, namely interviews, observation, and documentation. The implementation of the public relations strategy by the Surakarta DPRD public relations has implemented three stages. However, there are problems in the evaluation or monitoring section of the use of Instagram social media, which has been proven through a SWOT analysis. The SWOT analysis identifies the strengths, weaknesses, opportunities, and threats of each strategy used in this study. Key word: Public Relations Strategy, Public Relations DPRD Surakarta, Instagram